Предмет: Алгебра,
автор: nikylya54
розв’яжіть рівняння
3x2-(2x+1)(x+5)=(x+2)(x-4)+12
Ответы
Автор ответа:
12
Ответ:
x = -1
Объяснение:
3x^2-(2x+1)(x+5)=(x+2)(x-4)+12
3x^2 - 2x^2 - 10x - x - 5 = x^2 - 4x + 2x - 8 + 12
3x^2 - 2x^2 - 10x - x + 4x - 2x = 12 - 8 + 5
-9x = 9 *(-1)
9x = -9 / 9
x = -1
Похожие вопросы
Предмет: Математика,
автор: Snowman12345
Предмет: Обществознание,
автор: Кристинка2808
Предмет: Физика,
автор: pain5544roman
Предмет: Математика,
автор: нина1221
Предмет: Математика,
автор: нина1221